Concurrent Takayasu Arteritis and Vascular Ehlers–Danlos Syndrome: A Case Report - Hashimoto, Kyota; Sakai, Ryota; Shibata, Akiko; Okada, Yusuke; Yoshinaga, Syoichi; Kurasawa, Takahiko; Kondo, Tsuneo; Amano, Koichi (Frontiers in Cardiovascular Medicine, 2022)
Takayasu arteritis (TAK) is a rare primary systemic inflammatory vasculopathy. It is classified as a large-vessel vasculitis and is known to cause inflammatory aneurysms and vascular stenosis. Vascular Ehlers–Danlos syndrome (vEDS) is an autosomal dominant condition known to cause multiple aneurysms and arterial dissection at a young age owing to a mutation in the gene for type III collagen, COL3A1. Here, we present a case of TAK associated with vEDS with the development of multi-organ infarction of the brain, kidney, and spleen owing to multiple arterial aneurysms and stenosis of the internal carotid artery. The patient was successfully treated using anti-inflammatory agents, glucocorticoids, and tocilizumab with the addition of interventional radiology. In our case, a high inflammatory response led to vasculitis being the main cause of the disease with concurrent vEDS. When patients develop multiple aneurysms, stenosis, and dissections leading to multiple organ infarctions, a systemic differential diagnosis to consider concurrent vasculitis syndrome and non-inflammatory vasculopathy, including hereditary disorders, is important even with time constraints.